#TITLE_ALTERNATIVE# - Rachmat (NIM 122 02 023), Basuki
Abstract: A laboratory observation using water and air have been developed to observe the role of concentric pipe in gas lift performance. It was built with 3.8 m tubing length, 2 inchi tubing diameter, and a reservoir. Observation was conducted for 0.6, 0.9, 1.1 and 1.9 cm concentric pipe diameter. Experiment result was found that applying concentric pipe can increase the water production only at low injection pressure. Using the same model, the role of concentric pipe at lower reservoir pressure will be observe. Experiment built with three reservoir height, 3.4, 2.85, and 2.4 m. Observation conducted for 1.7, 2.17, and 2.63 cm concentric pipe diameter. Experiment result was observed by plotting water production against pressure of air injection. It was found that for 3.4 and 2.85 m reservoir height has same result with the observation before, increase of liquid production at low injection pressure. However, the result for 2.4 m reservoir height found that the liquid production will increase by increasing the diameter of concentric pipe. In this study was also predicted the role of static liquid level as effect of reservoir pressure for the effective of gas lifting system.